English Communication Challenges and Coping Strategies of Thai Call Center Staff in a European Airline Group - Michael, Kris Lietz; Lietz, Ginn; Noicharoen, Nopparat; Natee, Nitayanan (International Journal of Multidisciplinary in Management and Tourism, 2026)
This study investigates English communication challenges and coping strategies among Thai staff at a European airline call center, grounded in the framework of English for Specific Purposes (ESP). The objectives were to identify specific communication problems and to examine strategies employed for immediate problem-solving and long-term development. A mixed-methods design was utilized with 31 respondents selected via convenience sampling. Data were collected using a five-point Likert scale questionnaire and semi-structured interviews, then analyzed using descriptive statistics and content analysis. The results indicated that overall problems in listening, speaking, reading, and writing occurred at a rare to moderate frequency (M=2.32 to 2.72). Key challenges included understanding diverse accents and using appropriate professional vocabulary. Regarding strategies, staff primarily employed compensatory strategies such as focusing on keywords and using online translation tools for immediate issues. For long-term development, cognitive and metacognitive strategies like consuming English media were reported, though systematic training participation was limited. The findings suggest a need for integrating explicit strategy training into ESP courses and call center onboarding programs.